2015
DOI: 10.1007/s10971-015-3862-6
|View full text |Cite
|
Sign up to set email alerts
|

Conventional surfactant-doped poly (o-anisidine)/GO nanocomposites for benzaldehyde chemical sensor development

Abstract: We report on the synthesis of conventional surfactant dodecylbenzenesulfonic acid-doped poly (o-anisidine)/graphene oxide composite (DPOMA/GO), a orthomethoxy substituted derivative of anisidine, by in situ oxidative polymerization method. A mixture of Na 2 S 2 O 8 in HCl was used as oxidant, while dodecylbenzenesulfonic acid was used as both dopant and surfactant. The physicochemical characterization was carried out using a field-emission scanning electron microscope and X-ray crystallography (XRD), Fourier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…BZ is the most commonly used aromatic aldehyde in industry and is an important chemical raw material, but excessive inhalation of BZ will cause damage to nervous system. [ 10‐14 ] Similarly, antibiotic pollutants are also typical toxic organic pollutants in wastewater, because the misuse and uncontainable use of antibiotics bring out harsh antibiotic resistance. The misuse of TC in stock farming and aquaculture has resulted in excessive levels of TC residues in soil and water.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…BZ is the most commonly used aromatic aldehyde in industry and is an important chemical raw material, but excessive inhalation of BZ will cause damage to nervous system. [ 10‐14 ] Similarly, antibiotic pollutants are also typical toxic organic pollutants in wastewater, because the misuse and uncontainable use of antibiotics bring out harsh antibiotic resistance. The misuse of TC in stock farming and aquaculture has resulted in excessive levels of TC residues in soil and water.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…U sually, benzaldehyde is mainly used as a plasticizer and a solvent, but it is also used as a fragrance and flavoring in pharmaceuticals, food, cosmetics, etc. 1 However, some studies have recently found that benzaldehyde can induce genotoxic and mutagenic effects. 2 The presence of benzaldehyde above the normal permissible limit will not only affect people's health but also can seriously contaminate the environment.…”
mentioning
confidence: 99%
“…Usually, benzaldehyde is mainly used as a plasticizer and a solvent, but it is also used as a fragrance and flavoring in pharmaceuticals, food, cosmetics, etc . However, some studies have recently found that benzaldehyde can induce genotoxic and mutagenic effects .…”
mentioning
confidence: 99%
“…Benzaldehyde (BZ) and salicylaldehyde (SA) are essential industrial raw materials in the sectors of pharmaceuticals, dyes, spices, and resins, as well as the most often used aromatic aldehydes in industry . However, when BZ and SA leak into the environment, they will seriously pollute the atmosphere, not only causing serious negative impacts on aquatic organisms and ecosystems but also endangering human health. If inhaled too much, it can cause severe respiratory irritation, nerve paralysis, acute poisoning, etc . BZ and SA have genotoxic and mutagenic effects, which are identified as toxic chemicals by many countries.…”
Section: Introductionmentioning
confidence: 99%